Forest microhabitats differentially influence seedling phenology of two co-existing Mediterranean oak species - Monnier, Yogan; Prévosto, Bernard; Ripert, Christian; Corbani, Aude C.; Fernandez, Catherine (Journal of Vegetation Science, 2012)
Question How do forest microhabitats impact seasonal microclimate conditions and phenological seedling strategies in two co-occurring Mediterranean Quercus species with different leaf habits? Location Pinus halepensis woodlands, Provence, SE France. Methods Ninety sets of three acorns of Quercus ilex (evergreen) or Quercus pubescens (winter-deciduous) were sown under various P. halepensis canopy cover conditions. Canopy cover and litter depth were measured at each sowing point, and soil moisture and temperature were measured twice monthly. Seedling phenology and aerial development were monitored during the second growing season under different microhabitats. Results During rainy periods, soil moisture was higher under open canopy and thinner litter layers, whereas during summer drought soil moisture was higher under dense canopy and thicker litter layers. Quercus pubescens seedlings had higher growth activity than Q. ilex before summer drought, whereas the pattern reversed during autumnal growth. Dense canopy cover strongly delayed budburst and decreased foliar development in Q. pubescens, which was more affected than Q. ilex. Depending on species phenology, litter thickness can influence height growth of flushes during early summer. Conclusions Quercus pubescens has a phenological strategy to allow development of maximal foliar area before summer drought, a typical growth strategy of Mediterranean winter-deciduous species. In contrast, later phenological activity of evergreen Q. ilex enables it to cope with the dry period and capitalize on autumnal precipitation events. Dense cover acts as shelter in the dry season but can reduce soil moisture during wetter seasons. In contrast to Q. ilex, Q. pubescens appeared strongly dependent on canopy cover, suggesting that Q. ilex has a larger regeneration niche in Aleppo pine woodlands. In the context of global change, this ‘microhabitat effect’ on species-specific phenological strategy underlines the need to consider effects of local environmental conditions on regenerating species.
Keywords: Canopy; litter; Phenology; Quercus ilex; Quercus pubescens; Soil moisture; Survival